Isolating Accounting Variances Via Partitioned Matrices. - Corcoran, A. Wayne; Leininger, Wayne E. (The Accounting Review, 1975)
Shows that cost variance analysis, gross profit analysis and analysis of changes in value-based income determination may be treated in an identical manner by partitioned matrices. Advantages of employing matrices; Popularity of using matrix algebra in accounting.